Antitumor activity of (R, R')‐4‐methoxy‐1‐naphthylfenoterol in a rat C6 glioma xenograft model in the mouse. Issue 2 (5th December 2013) - Bernier, Michel; Paul, Rajib K.; Dossou, Katina S. S.; Wnorowski, Artur; Ramamoorthy, Anuradha; Paris, Arnaud; Moaddel, Ruin; Cloix, Jean‐François; Wainer, Irving W.
Abstract (R, R')‐4‐methoxy‐1‐naphthylfenoterol (MNF) inhibits cancer cell proliferation in vitro through cell‐type specific modulation of β2‐adrenergic receptor and/or cannabinoid receptor function. Here, we report an investigation into antitumor activity of MNF in rat C6 glioma cells. The potent antiproliferative action of MNF in these cells (IC50 of ~1 nmol/L) was refractory to pharmacological inhibition of β2‐adrenergic receptor while a synthetic inverse agonist of cannabinoid receptor 1 significantly blocked MNF activity. The antitumor activity of MNF was then assessed in a C6 glioblastoma xenograft model in mice. Three days after subcutaneous implantation of C6 cells into the lower flank of nude mice, these animals were subjected to i.p. injections of saline or MNF (2 mg/kg) for 19 days and tumor volumes were measured over the course of the experiment. Gene expression analysis, quantitative RT‐PCR and immunoblot assays were performed on the tumors after treatment. Significant reduction in mean tumor volumes was observed in mice receiving MNF when compared with the saline‐treated group. We identified clusters in expression of genes involved in cellular proliferation, as well as molecular markers for glioblastoma that were significantly downregulated in tumors of MNF‐treated mice as compared to saline‐injected controls. The efficacy of MNF against C6 glioma cell proliferation in vivo and in vitro was accompanied by marked reduction in the expression of cell cycle regulator proteins. This study is the first demonstration of MNF‐dependent chemoprevention of a glioblastoma xenograft model and may offer a potential mechanism for its anticancer action in vivo.